Assessment of nitrogen and phosphorus pollution based on multi-source data and the InVEST model in the Henan section of Yellow River Basin, China - Yang, Xu; Qiu, Shike; Wang, Chao; Du, Jun; Zhang, Xinli; Sun, Tingting (Frontiers in Environmental Science, 2024)
In recent years, non-point source pollution (NPSP) has become prominent in the Yellow River Basin (YRB) of China, and seriously affects human survival and sustainable development. The Henan section was selected as an example region of Yellow River Basin (YRB) in China, and the Integrated Valuation of Ecosystem Services and Tradeoffs (InVEST) model has been used to quantitatively evaluate the nitrogen (N) and phosphorus (P). The results show that (1) the cultivated land, grassland and unused land decreased, while forest land, water areas and built-up areas increased in 2000-2020; and the precipitation increased from the northeast to the